1987
DOI: 10.1104/pp.84.2.433
|View full text |Cite
|
Sign up to set email alerts
|

A Tight-Seal Whole Cell Study of the Voltage-Dependent Gating Mechanism of K+-Channels of Protoplasmic Droplets of Chara corallina

Abstract: The biophysical properties of voltage-dependent K+-channels of pro- (e.g. 8, 19, 26, 27), and that potassium ions are the main species transported in the leakage current (2). K+-channels also play a role in the light-induced membrane potential change in perfused Chara corallina cells (30) and in Eremosphaera viridis (17). Ion transpot through the plant cell membrane has also been studied by noise analysis of the membrane potential (6,(22)(23)(24). The minus two slope of the voltage noise power spectrum has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The membrane enclosing these cyto plasmic droplets has been shown to be tonoplastic in origin (Sakano & Tazawa 1986;Liihring 1986), although this remains controversial (cf. Homble 1987). For example, Krawczyk (1978) observed single 10 pS, non-selective monovalent cation channels (with 100 mM solutions), most active at depolarized potentials, in mem brane patches formed after insertion of a microelectrode into Nitella cytoplasm, similar to the channel reported here.…”
Section: Comparison With Other Plant Channelssupporting
confidence: 71%
See 1 more Smart Citation
“…The membrane enclosing these cyto plasmic droplets has been shown to be tonoplastic in origin (Sakano & Tazawa 1986;Liihring 1986), although this remains controversial (cf. Homble 1987). For example, Krawczyk (1978) observed single 10 pS, non-selective monovalent cation channels (with 100 mM solutions), most active at depolarized potentials, in mem brane patches formed after insertion of a microelectrode into Nitella cytoplasm, similar to the channel reported here.…”
Section: Comparison With Other Plant Channelssupporting
confidence: 71%
“…Outward K currents from membrane-bound cytoplasmic droplets of the giant algal cells N i t e l l a and Chara have been also found (Liihring 1986 ;Homble 1987;Homble et al 1987;Laver & Walker 1987). The membrane enclosing these cyto plasmic droplets has been shown to be tonoplastic in origin (Sakano & Tazawa 1986;Liihring 1986), although this remains controversial (cf.…”
Section: Comparison With Other Plant Channelsmentioning
confidence: 99%
“…In contrast, Minorsky et al (1989) found cation selective channels patch clamped in the onoplast of the same species, Saccharomyces cerevisiae, were insensitive to large changes in the 'cytoplasmic' Ca^^ activity. '• K^ channels in cytoplasmic droplets from charophytes channels have been frequently measured in cytoplasmic droplets (see V. 2) from cells of Chara allina {l^uhring, 1986;Homble, 1987;Homble, Ferrier & Damty, 1987;Laver & Walker, 1987;l>erman & Findlay, 1989 a;Bertl, 1989;Bisson, Tyerman & Findlay, 1989;Katsuhara, Mimura o^ Tazawa, 1989;Laver et al, 1989). The most common channel in the droplet membrane is voltage dependent, has a high unitary G (about 170 pS in 150 mM KCl), and is generally strongly selective for K+ (Luhring, 1986;Laver & Walker, 1987;Bertl, 1989;leaver etal., 1989;Katsuhara et al, 1989).…”
Section: K^ Channels In Yeast Tonoplastmentioning
confidence: 99%
“…Cytoplasmic droplets formed from Chara are covered by a membrane derived from the tonoplast (Lihring, 1986;Sakano and Tazawa, 1986). The passive conductance ofthis vacuolar membrane is largely dominated by a potassium conductance (Homble, 1987).…”
Section: Introductionmentioning
confidence: 99%